Prevalence of Ocular Morbidities and its Socio-demographic correlates in an urban slum of western Uttar Pradesh, India - Chadha, Sumeet; Kumar, Shailendra; Singh, Jai Veer; Sehgal, Shruti; Baijal, Vijay; Raghav, Santosh Kumar (Indian Journal of Community Health, 2016)
Background: Ocular Morbidities with its economic and social consequences, represents an important public health problem in various parts of the world. Aims & Objective: 1. To find out the prevalence of Ocular Morbidities in relation to socio-demographic correlates in an Urban Slum of District Muzaffarnagar of Uttar Pradesh. Material & Methods: This community based cross – sectional study was carried out among 1603 individuals from 341 families selected by simple random technique in field practice area of Urban Health Training Centre, Makkinagar, Khalapar, Muzaffarnagar. The present study focuses on ocular examinations and diagnosis of ocular morbid conditions which were prevalent in that selected area. The information was collected on a pre-designed and pretested questionnaire. Results: The prevalence of ocular morbidities in the study group was found to be 50.0% with significantly much higher in the age group 60 years and above. The major cause ocular morbidities were refractive errors (84.8%), followed by cataract (19.8%). The prevalence was significantly more in widows/widower (73.7%) than other groups of marital status (48.5%); upper socio – economic status (74.4%) than other groups of socio-economic status (48.7%), joint family (56.3%) than nuclear family (40.7%) and Muslim community (52.1%) than Hindu community (42.6). Conclusion: In this present study the prevalence of ocular morbidities was found to be 50.0% in the population with a marginal higher prevalence in females (52.4%) as compared to the males (47.8%). The most common cause was refractive errors followed by cataract. The ocular morbidities were significantly associated with age, marital status and socio-economic status. There was no significant correlation with educational status and occupations of the patients.